Psikoedukasi Cyberbullying Terhadap Remaja - Anissa Regita Putri; Nor Fatmah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Social media creates a flow of positive and negative information. Negative content can impact juvenile delinquency, one of which is cyberbullying or indirect violence through social media that targets the victim's mental state. This study asks to what extent psychoeducation can improve adolescents' understanding of the impact and dangers of cyberbullying. The purpose of this study was to determine the effect of psychoeducation on cyberbullying behavior in adolescents. This research method used a qualitative pre-test and post-test to measure the understanding of the material obtained by 32 adolescents. The results showed changes in the material, thinking, and knowledge of adolescents. After psychoeducation on cyberbullying behavior through the provision of psychoeducation can improve good behavior in adolescents.